Sosialisasi Pemanfaatan Caklingking Sebagai Salah Satu Media Pembelajaran Siswa SD - Eka Rachma Kurniasi; Hevitria Hevitria; Sisi Pitriyana; Meilidiya Fuziani; Wulandari Wulandari; Fiki Alghadari (Jurnal Abdimas Prakasa Dakara, 2021)
Caklingking is one of the traditional games that used to be played a lot. Usually caklingking is played together and uses stones that are formed to be played. Based on the problems in the field, that students no longer play caklingking in everyday life. In addition, students do not know that caklingking can be a medium for learning mathematics. Because of this problem, it is necessary to socialize the use of caklingking in elementary school student learning and the use of this game in daily life. The purpose of this service is to socialize the use of caklingking in elementary school student learning and the use of this game in everyday life. The implementation method used is to provide direct socialization to students of knowledge about the use of caklingking. This activity was attended by 20 students of SDN 14 Pangkalpinang. This outreach activity has been successfully implemented.